(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
Biochar application to soil is important for crop production and productivity in Ethiopia mainly where high rainfall is available. This study was conducted in Jimma University College of Agriculture and Veterinary Medicine campus during 2019 cropping season to determine the effect of cow urine and water quenched biochar with the biochar application rate on wheat yield and yield components. A wheat pot experiment was sown with two biochar rates (6 t ha-1 and 4 t ha-1 quenched with (cow urine and water). The number of effective tillers, spike length, seeds per spike, above dry biomass and thousand seed weight revealed non-significant differences. However, plant height, yield per pot and harvest index indicated significant variation due to the treatment combination of cow urine quenched, water quenched biochar and biochar rate over the control treatment. Six (6) tones biochar quenched with cow urine showed the maximum result and followed by 4 tones biochar quenched with cow urine. Biochar application has a significant advantage over control treatment. Int. J. Agril. Res. Innov. Tech. 10(1): 35-39, June 2020